2017
DOI: 10.1007/978-3-319-66393-7_6
|View full text |Cite
|
Sign up to set email alerts
|

Inclusive Recruitment? Hiring Discrimination Against Older Workers

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
29
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(32 citation statements)
references
References 24 publications
(43 reference statements)
2
29
0
1
Order By: Relevance
“…Further replication in a sample of blue‐collar workers will be beneficial as our results may potentially have greater relevance to the blue‐collar sector. Past research has indicated that older job applicants may face greater barriers to blue‐collar jobs compared to white‐collar jobs because of the expectation that physical performance necessarily declines with age (Drydakis et al., 2017; Oesch, 2020). At the same time, a meta‐analysis demonstrated that age was only weakly related to poor physical health, and argued that more serious conditions, such as cardiovascular disease, typically occur only after retirement (Ng & Feldman, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Further replication in a sample of blue‐collar workers will be beneficial as our results may potentially have greater relevance to the blue‐collar sector. Past research has indicated that older job applicants may face greater barriers to blue‐collar jobs compared to white‐collar jobs because of the expectation that physical performance necessarily declines with age (Drydakis et al., 2017; Oesch, 2020). At the same time, a meta‐analysis demonstrated that age was only weakly related to poor physical health, and argued that more serious conditions, such as cardiovascular disease, typically occur only after retirement (Ng & Feldman, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Whether a positive action will bring outcomes is a government’s big challenge. Social dialogue between policy makers, unions and employers might be required for coordinated workplace actions to integrate vulnerable population groups (Drydakis et al , 2017).…”
Section: Discussionmentioning
confidence: 99%
“…There are various explanations for the low employment rates for people between the ages of 55 and 64, one of which is age discrimination in hiring. Previous research has found considerable evidence of age discrimination in hiring in the United States (Johnson & Neumark, 1997;Lahey, 2008;Farber, Silverman, & von Wachter, 2016;Neumark, Burn, & Button, 2016, 2019Neumark, Burn, Button, & Chehras, 2019;Neumark, 2018), the United Kingdom (Riach & Rich, 2010;Tinsley, 2012;Riach, 2015;Drydakis, 2017), and the European Union (Riach, 2015;Baert, Norga, Thuy, & Van Hecke, 2016;Carlsson & Eriksson, 2017). 1 Hiring discrimination pushes older workers out of the labour market, forcing many to claim retirement benefits prior to full retirement age.…”
Section: Introductionmentioning
confidence: 99%